ADAPTASI MORFOLOGI DAN FISIOLOGIS TANAMAN PADI SAWAH TERHADAP CEKAMAN GENANGAN AIR - Fahrurrozi; Indah Mutiara Fadhillah; Khairunnisa Hidayati; Fatri Nur Hazana; Desi Lestari; Lia Fitriani; Lia Rahmi Anjani (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
Rice (Oryza sativa L.) is a major staple food crop in Indonesia whose production is highly vulnerable to flooding stress as a result of climate change. This article presents a systematic–narrative literature review examining scientific publications from the past ten years concerning the morphological and physiological responses of rice plants to flooding stress. The synthesis indicates that the main adaptive mechanisms of rice include the formation of aerenchyma tissue and adventitious roots, regulation of stem elongation (escape and quiescence strategies), and activation of anaerobic metabolism regulated by the SUB1A and SNORKEL1/2 genes. These mechanisms have been reported to enhance plant survival and maintain rice yield by approximately 20–40% compared with flood-intolerant varieties. An integrated understanding of these adaptive responses has important implications for the breeding of flood-tolerant rice varieties, adaptive water management in paddy fields, and the development of cultivation strategies in flood-prone areas to maintain rice production stability and support national food security amid climate change.